SURVEY ON THE OCCURRENCE OF VIRUSES INFECTING CUCURBITS INYOGYAKARTAANDCENTRALJAVA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT Cucurbits are grown throughout the Java Island as dry season crops. Plants having mosaic, mottling, chlorosis and leaf distortion symptoms were frequently found in most of the cucurbit fields during the survey which conducted in Central Java including Sleman,Kulon Progo, and Klaten during July-September 2000 and 2001. Usingdouble antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA)